2022
DOI: 10.1177/17479541221106378
|View full text |Cite
|
Sign up to set email alerts
|

Performance indicators in women’s volleyball Olympics and World Championships (2014–2021)

Abstract: The aim of this study was to explore the match and technical indicators between winning and losing women's teams in the Olympics and World Championships (2016–2021) depending on the final score of the matches and to compare the winners’ technical indicators in 3-set matches to those of men in the respective competitions. A total of 281 volleyball matches were analyzed from the Women's Olympics (2016 and 2021) and World Championships (2014 and 2018). Discriminant function analysis determined which skill(s) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In regard to neuromuscular risk factors, movement task [ 33 ] and surface [ 34 ] might be crucial factors since volleyball can be performed indoors on hard surfaces and outdoors on sand surfaces. Both disciplines are part of the Olympic games [ 35 , 36 ]. Information on neuromuscular control in spike jumps in healthy and injured athletes is not available, neither on hard surfaces such as in a hall nor in sand conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In regard to neuromuscular risk factors, movement task [ 33 ] and surface [ 34 ] might be crucial factors since volleyball can be performed indoors on hard surfaces and outdoors on sand surfaces. Both disciplines are part of the Olympic games [ 35 , 36 ]. Information on neuromuscular control in spike jumps in healthy and injured athletes is not available, neither on hard surfaces such as in a hall nor in sand conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Looking ahead, future research directions could further explore the direct measurement of lower limb muscle strength and its relationship with jump height in women volleyball players. Additionally, integrating advanced biomechanical analyses, such as motion capture technology, could elucidate the underlying mechanisms driving the observed associations between anthropometric parameters, muscle strength, and jump height (Donahue et al, 2023;Giatsis., 2023). This study illuminates the intricate relationship between height, weight, BMI, muscle strength of the lower limbs, and jump height among women volleyball players, challenging traditional assumptions and highlighting the multidimensional nature of athleticism in the sport.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies related with volleyball (Giatsis et al, 2022;Giatsis, 2022) suggested that organizers could modify the match report by including additional data, such as the attack efficiency. In the present match report, attack opponent errors, serve errors and other errors included in the data presented.…”
Section: Discussionmentioning
confidence: 99%
“…However, basic statistics can be easily applied into court training sessions (Mackenzie and Cushion, 2013). Various studies that have been done in other sports as volleyball using match report, data revealed that even with simplified statistics it is possible to find the performance indicators that determine the winners from the losers in the matches (Giatsis et al, 2022;Giatsis, 2022). However, more detailed match reports using software could present a clearer picture of the game, while the analysis of individual sets would also give a clearer picture of the performance of teams and players.…”
Section: Introductionmentioning
confidence: 99%